Information technology and collection management for library user environments - Walker, Joseph, 1981-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book brings into focus the new responsibility libraries have in meeting patron needs, specifically with the use of emerging technologies, highlighting the concepts of collection management, library space planning, and information technologies"--Provided by publisher.
Introduction: motivations and a brief historical review of "information technology" leading up to the information age -- Developing an approach and methodology for the continued progress of library studies and information management -- Collection spaces and management, virtual and physical, in the user environment -- Survey of information technologies in the user environment -- Universal index for information collections, physical and virtual: information experts merging IT and collection management for real solutions in the user environment -- Space managing system for the physical collection: information experts merging IT and collection management for real solutions in the user environment -- Database system for the virtual collection: information experts merging IT and collection management for real solutions in the user environment -- Information expertise and the vision of future library institutions and user environments -- Institution case study: Charleston County Public Library, Main Branch / J. Walker -- Library showcase: San Luis Obispo County Library, Cayucos Branch: interview with Melody Mullis / Lisa Block -- Institution case study: Google Books / J. Walker -- Library showcase: Darien (Conn.) Library: interview with Alan Gray / Lisa Block -- Institution case study: ITT Technical Institute, Atlanta Campus / Lisa Block -- Library showcase: DeKalb County (GA) Public Library, Toco Hill Branch: interview with Darro Wiley / Lisa Block -- Institution case study: Project Gutenberg / J. Walker -- Library showcase: Enoch Pratt Free Library, Roland Park Branch: interview with Alexander Design Studio / Lisa Block, J. Walker -- Institution case study: Robert W. Woodruff Library, Emory University / Lisa Block, J. Walker -- Library showcase: Houston Public Library, Morris Frank Branch: interview with Wendy Heger / Lisa Block -- Institution case study: ThinkQuest Library / J. Walker -- Library showcase: Dauphin County Library System, Hummelstown Community Library: interview with Wendy Mosteiko/Alexander Design Studio / Lisa Block -- Institution case study: YouTube / J. Walker -- Library showcase: Lupton Library, Univ. of Tenn. at Chattanooga: interview with Jason Griffey / Lisa Block -- Library showcase: Manhattan Christian College, Kansas: interview with Mary Ann Buhler / Lisa Block -- Library showcase: the Mathewson-IGT Knowledge Center at the University of Nevada, Reno: interview with Carol Parkhurst / Lisa Block -- Library showcase: New Castle Public Library: interview with Katie Newell / Lisa Block -- Library showcase: Norlin Library, University of Colorado: interview with John Culshaw / Lisa Block -- Library showcase: Ramsey County Roseville Library: interview with staff / Lisa Block -- Library showcase: Sacramento Public Library, Belle Cooledge Library: interview with Lois Casement Ross / Lisa Block, J. Walker -- Library showcase: Sterling C. Evans Library, Texas A&M University: interview with staff / Lisa Block -- Library showcase: Virginia School for the Deaf and Blind: interview with Margaret Robison / Lisa Block, J. Walker.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 03/22/2014).
Keywords: Collection management (Libraries); Libraries -- Space utilization; Libraries -- Information technology; Libraries -- Special collections -- Electronic information resources; Digital technologies & complex discrete systems; Information management and access; Libraries as learning space; Publication digitalization; Social interaction in patron communities; Electronic books